Role of school preparedness on children's in-person schooling decision during Covid-19 pandemic in Bangladesh - Tasnim Murad Mamun; Mukta Akter; Rozina Akter; Md. Tanzeer Alam; Khan Mehedi Hasan; Rakib Hossain (Elsevier, 2023)
Background: Due to Covid-19 impacted disruption, Bangladesh government had temporarily shut all the educational institutes down in March 2020 though it was prolonged until September 2021. After continuous concern of UNICEF, when government considered about reopening of schools for in-person classes amid the pandemic, many parents were found to be worried regarding the status of school preparedness. Objective: The purpose of this study is to investigate compliance status of school preparedness as per UNICEF's guidelines and its effect on children's schooling decision during the pandemic. Methods: The study considers 30 primary schools and 310 parents by employing a simple random sampling technique in Dhaka city. Along with the descriptive analysis, principal component analysis (PCA) and a logistic regression model have been executed to come up the goal of the study. Results: The findings explore that classroom density, level of preparedness on health and hygiene, social distancing and awareness, reporting and referral mechanism, communication with school authority, and school arrival on foot have a positive association with the likelihood of parents' decision for sending their children back to school. On the other hand, monthly expenditure and distance from school to home have a negative relationship with the likelihood on sending children to in-person schooling. Conclusion: The level of school preparedness greatly affects the parent's decision for children's physical schooling during pandemic. So, to keep mental stability of the children amidst any pandemic, the authorities should take care on school preparedness to ensure physical schooling of the children.